Bruxism and other jaw loading behaviours are associated with somatic symptoms and psychological distress in orofacial pain-free adults: a cross-sectional study - Chuinsiri, Nontawat; Thammanichanon, Peungchaleoy; Puttaravuttiporn, Pornputthi; Mongkolchart, Wittawat; Chudet, Chadatorn; Thongraksri, Sirada (Frontiers in Oral Health, 2025)
BackgroundOral behaviours, both functional and non-functional, are commonly reported and can negatively impact oral health. Among orofacial pain patients, non-functional oral behaviours have been observed in association with elevated psychosocial factors. However, the extent to which these findings apply to individuals without orofacial pain remains inconclusive. This study examined the latent constructs of oral behaviours and their associations with somatic symptoms and psychological distress in orofacial pain-free adults.MethodsThis multi-centre cross-sectional study recruited 194 participants who were free of orofacial pain. All participants provided informed consent and completed a set of self-reported questionnaires, including the Oral Behaviour Checklist-21, the Patient Health Questionnaire (PHQ)-15 for assessing somatic symptoms and the PHQ-4 for assessing psychological distress. Exploratory factor analysis (EFA) was conducted to identify latent constructs underlying the observed questionnaire item responses. Correlations between questionnaire scores were assessed using the Spearman's rank correlation test. A p value of less than 0.05 was considered statistically significant.ResultsThe mean age of participants was 24.6 ± 6.2 years, and 70% were female. Exploratory factor analysis identified three distinct latent constructs of oral behaviours: tooth-contact bruxism, non-tooth-contact bruxism and other jaw loading behaviours. Overall oral behaviours, sleep-state behaviours, awake-state behaviours and the EFA-derived constructs showed statistically significant positive correlations with both somatic symptoms and psychological distress.ConclusionsIn addition to being classified by sleep and awake states, oral behaviours can be grouped into tooth-contact bruxism, non-tooth-contact bruxism and other jaw loading behaviours. The significant correlations observed among oral behaviours, somatic symptoms and psychological distress suggest that individuals reporting frequent oral behaviours should be further evaluated for underlying psychosocial factors, even in the absence of orofacial pain.